Inversor de 49 níveis utilizando células CHB-2CB em cascata conectado à rede elétrica - Vasconcelos, Paulo Salim Daher (2018)
This dissertation aims to develop a controller to a multilevel inverter with 49 level voltage output connect to the electric grid, adapting an inverter capable of generate a staircase signal voltage source to work as current source. For this purpose, three possibilities to the bidirectional power flow control were presented: the first one uses the phase-shift between the inverter output fundamental voltage and the grid voltage; the second one uses a closed-loop proportional control with the grid feedforward; and the third one is a closed-loop proportional control with the grid and the reference feedforward. All the three methods were simulated and the choose one was the closed-loop proportional control with the grid feedforward for being easier to be implemented. The developed controller was implemented at a 1 kW prototype and presented a good performance at bi-directional inverter power flow operation.